A new species of Proctophyllodes Robin, 1868 (Acari: Proctophyllodidae) from two tanagers of the genus Piranga Vieillot (Passeriformes: Cardinalidae) from North America - Hernandes, Fabio Akashi [UNESP]; OConnor, Barry M.; Bauchan, Gary R.; Ochoa, Ronald (Taylor & Francis Ltd, 2017)
A new feather mite species, Proctophyllodes pirangae sp. n. (Acari: Proctophyllodidae) is described from two tanagers of the genus Piranga Vieillot, 1808 (Passeriformes: Cardinalidae) in North America: the Scarlet Tanager, Piranga olivacea (Gmelin) and the Western Tanager, Piranga ludoviciana (Wilson) (Passeriformes: Cardinalidae) from North America. The new species belongs to the anthi species group and differs from the most similar species, Proctophyllodes polyxenus Atyeo and Braasch, by having in males, the aedeagus and genital sheath extending to or slightly beyond the level of setae g, the anterior margin of the opisthogastric shield shallowly concave, and its posterior margin nearly square-shaped, and the lamellae smaller; in females, both the lobar cleft and the transverse band of soft tegument at level of setae h1 are considerably narrower.
Keywords: Feather mites; Acari; systematics; ectoparasites; avian mites